霹雳州金宝县伍英芳的商业及社会参与（1901—19750) - 陈, 黎 (2023)
伍英芳（1901-1975）出生于槟城，第一次世界大战时曾留学英国和 香港，1925 年来到金宝后开始了长达 40 多年的矿务发展。从 1930 年代开 始参与社会活动，伍英芳先后在古冈州会馆和金宝接生院担任职务，1950 年左右是伍英芳事业发展的高峰，在政府和民间组织都担有职位，1965 年后慢慢淡出社会活动舞台。 本论文主要采用文献分析、访谈和实地考察方法，探讨伍英芳在金宝 的商业发展、社会参与、民生关怀与认同问题。 伍英芳眼光独到，具体表现在多种经营上，伍英芳所经营的产业，既 有矿地，也有附属商业如代理金宝第一家油站美孚行各类汽油、金宝最大 华人铁厂之一的协力铁厂，以及金宝工人居住地鸿栈园的房地产等行业。 由于金宝是锡矿重镇，伍英芳的商业发展面对的最大挑战就是锡锭限购， 多种经营的方式让伍英芳商业活动可以维持下去。 伍英芳在经商的同时，也积极参与了金宝的社会活动，对金宝华人社 会面临的生老病死等民生问题都给予了持续的关注。以新村迁移、金宝古 庙华人义冢联合会和金宝接生院为例，无论是参与政府部门，还是民间组织，伍英芳都扮演着联结官民的桥梁角色。 伍英芳积极参与社会活动的背后涉及到华人的认同，伍英芳的认同主 要涉及同乡情、国家认同和文化认同。伍英芳参与地缘会馆，做到了统筹 安排照顾乡梓的初衷。他作为金宝地方华人领袖，曾积极参与金宝华人州 籍民的公民权申请的准备工作。伍英芳曾参与金宝公立女子和金宝中华学 校成为国民型小学过程，在保留华文教育的基础上，为金宝学生提供学习 英语机会，这有助于学生未来职业的发展。 伍英芳是金宝当地的华人领袖，凭借眼光独到，苦心经营商业 40 多 年。在金宝社会活动中，对华人社会民生问题给予了长久的支持。可以说， 伍英芳是关怀社会的华人地方领袖。The paper studies Kampar tin miner Ng Yin Fong (1901-1975), who was born in Penang and studied in Britain and Hong Kong during the first World War. He came to Kampar in 1925 and began mining industry for more than 40 years. From the 1930s, Ng Yin Fong began to enter the public’s field, first Koo Kong Chow Association, then Kampar Chinese Public Maternity hospital. Around 1950, Ng Yin Fong’s career peaked. He held important positions in the government and non-governmental organizations, and gradually faded out of the public after 1965. This paper mainly adopts the methods of literature research, interview and field investigation to explore Ng Yin Fong ’s business development, social participation and contribution and identity in Kampar. Ng Yin Fong has a unique vision, which is embodied in diversified operation. Ng Yin Fong’s industries include both mining land and affiliated businesses, such as Esso station, Heep Leck Sun Kee Foundry, real estate and other industries. Esso station is the first oil station of Kampar, and Heep Leck Sun Kee Foundry is one of the largest Chinese foundry of Kampar, and Chop Hoong real estate is the residence of Kampar workers. As Kampar is an important tin mining town, the biggest challenge for Ng Yin Fong’s business development is Tin Control Scheme. Diversified management can sustain Ng Yin Fong’s business activities for more than 40 years. Ng Yin Fong participated in Kampar’s social activities and paid continuous attention to the livelihood problems faced by Kampar Chinese society, such as birth, old age, illness and death. Ng Yin Fong paid more attention to Kampar Koo Kong Chow Association and Kampar Chinese Public Maternity hospital, as well as the migration of new villages after the Japanese rule. Whether participating in government departments or Malaysia Chinese Association, Ng Yin Fong always played a bridge role between officials and the people. Behind Ng Yin Fong’s active participation in social activities is his Chinese identity. Ng Yin Fong’s identity mainly include the feeling towards China, national identity and cultural identity . As a local Chinese leader in Kampar, Ng Yin Fong actively participated in the preparation of the citizenship application of Kampar Chinese state citizens. Besides, Ng Yin Fong paid attention to the education of Chinese schools. As the chairman of Kampar public girls' school and Kampar public Chinese school, Ng Yin Fong actively respond to the national language integration policy in the transformation of a national primary school, on the basis of retaining Chinese education, and provide Kampar students with opportunities to learn English, which provides language basic for the future career development. As a local Chinese leader, Ng Yin Fong pursued his businesses with his unique vision for more than 40 years. As to Kampar’s society, Ng Yin Fong gave long-term support to the livelihood issues of the local people. We can say that Ng Yin Fong is a Chinese tin miner and also a Chinese leader who cared for the local society.